Optimization analysis of production capacity on trimming process for passenger vehicle with a learning curve approach (case study: car os) - Franka Hendra; Riki Effendi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
The primary goal of this research to optimizing the production process capacity is expected to answer basic problems of how steps taken by the manufacturing industry to produce effective output. This study used a technique Research Design case study, namely in the automotive manufacturing industry in the process of assembling a car OS in the Trimming Process PT. XYZ. This study refers to the technique of quantitative research methods of data collection by interview and sampling cycle time by using stopwach. There are 5 models used in this research is, a) Learning Curve Approach, b) Time study c) The model of productivity to measure productivity Actual and after the application of the standard time Productivity Model, d) Efficiency and Efectivity Model. Results of this study found a) Learning Curve Effect on the curve for each station, the end effect of learning curve for operators learning process average in the assembly process units to 11 – 16 with learning rate between 88% - 94% for each stations, b) Standard time for assembly process OS is 215.17 minutes/units with the effective capacity 5.18 units / hour, c) Estimate the productivity level obtained when applying the standard time is 5.18 higher than the actual productivity is 2.45, d) the level of efficiency that can be achieved in the application of standard time is 4.7%, e) Identification of factors that affect the speed of the operator skill then found five factors that according to the operator (the respondents) that affect their work, the machine does not automatically chosen 95% of respondents, many elements of the work carried out by manual as much as 85% and 80% respectively of respondents choose the layout, engine support and salaries / wages are still not standard than other same industry.